2022
DOI: 10.1002/cbdv.202200728
|View full text |Cite
|
Sign up to set email alerts
|

Selected Aspects of Invasive Solidago canadensis with an Emphasis on Its Allelopathic Abilities: A Review

Abstract: Solidago canadensis L., native to North America, is now an invasive plant worldwide. Its abundant seeds, rapid vegetative reproduction ability, and allelopathy to other plants are the main reasons for its successful invasion. It has negative impacts on the ecological environment of the invaded area and causes a reduction in local biodiversity and economic losses of agriculture and stock farming. Each part of the plant contains a variety of allelochemicals (terpenoids, phenolics, and flavonoids), including a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Furthermore, several studies found that competition for light is an important mechanism regulating plant diversity and productivity (Borer et al, 2014; DeMalach et al, 2017; Hautier et al, 2009). However, we note that S. canadensis is allelopathic and could adversely affect subdominant plants, and in turn arthropods, through the release of chemicals that inhibit subdominant plant germination or growth (Yang et al, 2007; Yuan et al, 2013; Zhu et al, 2022). S. canadensis can have stronger allelopathic effects on other plant species in its invasive range (Yuan et al, 2013) but may still reduce the growth of other plants in its native range via allelopathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, several studies found that competition for light is an important mechanism regulating plant diversity and productivity (Borer et al, 2014; DeMalach et al, 2017; Hautier et al, 2009). However, we note that S. canadensis is allelopathic and could adversely affect subdominant plants, and in turn arthropods, through the release of chemicals that inhibit subdominant plant germination or growth (Yang et al, 2007; Yuan et al, 2013; Zhu et al, 2022). S. canadensis can have stronger allelopathic effects on other plant species in its invasive range (Yuan et al, 2013) but may still reduce the growth of other plants in its native range via allelopathy.…”
Section: Discussionmentioning
confidence: 99%
“…dominate roadsides and old fields across much of eastern North America (Abrahamson & Weis, 1997), and many Solidago spp. are invasive in Europe and Asia (Benelli et al, 2019; Jakobs et al, 2004; Zhu et al, 2022). The genus Solidago is a popular study system in community ecology to understand the three‐way interaction among plants, their herbivores, and the predators of those herbivores (Abrahamson & Weis, 1997; Crutsinger, Reynolds, et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Different parts of Solidago were assumed to differ in their allelopathic effect ( Marksa et al, 2020 ; Kato-Noguchi & Kato, 2022 ; Zhu et al, 2022 ). Allelopathic studies have most often used aboveground parts such as leaves, stems, and flowers, with leaves being most commonly found to have an effect ( Wang, Wu & Jiang, 2019 ; Wei et al, 2020a ; Wei et al, 2020c ; Zandi et al, 2020 ; Kato-Noguchi & Kato, 2022 ; Zhu et al, 2022 ). Direct comparisons revealed that aboveground parts of S. canadensis had a significant allelopathic effect, but the effect of belowground parts was not significant ( Yu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The content and type of phenolic compounds differ in plant tissues, including leaves, flowers, stem, and roots, and the characteristics can also be variable between S. canadensis and S. gigantea ( Marksa et al, 2020 ; Kato-Noguchi & Kato, 2022 ; Zhu et al, 2022 ). Further, even in the same species, the concentration of allelochemicals can differ based on location ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The Solidago canadensis L. weed poses a global threat to the environment as it spreads uncontrollably on roadsides, forests, fields, meadows and farmland [ 1 ]. Additionally, goldenrod releases toxic substances that suppress other plants (allelopathic effect), which leads to the displacement of wild ones [ 2 ].…”
Section: Introductionmentioning
confidence: 99%